Causes and trends of late diagnosis in Korean patients with hydroxychloroquine retinopathy - Ahn, Seong Joon; Kim, Ji Hong (Frontiers in Medicine, 2023)
Introduction Late diagnosis of hydroxychloroquine retinopathy remains a major concern, with the potential for irreversible visual impairment. This study aimed to investigate the causes of late diagnosis in a hospital-based cohort of Korean patients with hydroxychloroquine retinopathy and assess the trend of late diagnosis from 2015 to 2022. Methods Thirty-eight patients with a late diagnosis (severe stage at diagnosis) among 94 patients with hydroxychloroquine retinopathy were included in the analysis. The causes of late diagnosis were categorized as referral-related, patient-related, and screening-related factors. Results The most prevalent cause was no or late referral to ophthalmologists, contributing to a significant gap in timely identification. Patient-related causes included delayed monitoring visits despite scheduled appointments and early-onset disease. Screening-related causes encompassed an insufficient number of sensitive tests, leading to inadequate evidence for diagnosis, and missed or wrong diagnoses by screening physicians. The proportion of late diagnoses decreased over time, indicating improvements in overall screening and detection. The decreasing proportions of screening-related causes suggest advancements in screening practices and the use of multiple sensitive tests for screening. Discussion Efforts to further reduce late diagnoses and improve screening and diagnostic processes are necessary. Our data emphasize the importance of timely referral to ophthalmologists for early detection and management.